Screening of Humic Substances Extracted from Leonardite for Free Radical Scavenging Activity Using DPPH Method - Attila Csicsor; Etelka Tombácz (Molecules, 2022)
Humic substances (HSs) have been researched for a long time and still manage to surprise humanity today. According to the latest research, in addition to their previously well-known effects, they also have antioxidant properties. However, this previous research does not examine the difference in the antioxidant effect of the fractions extracted/produced in different processes; they do not consider the light absorption of the HSs, which falsifies analysis based on the measurement of color change over time. In the present work, HS fractions were obtained from leonardite, the extraction processes can also be implemented on an industrial scale. The fractions were characterized by elementary analysis, UV–Vis and FT-IR spectroscopies, to prove that our self-extracted samples have similar characteristics to the International Humic Substances Society (IHSS) standard samples. The different methods of HS fractionation affected the elemental composition, and the spectral characteristics. The antioxidant effect was investigated using the DPPH method to screen the antioxidant efficiency of humic, fulvic, and himatomelanic acids. In addition, we compared our results with the IHSS standard samples to obtain a more comprehensive picture of the antioxidant effect of HSs extracted in different ways according to the DPPH method. Based on our results, the extraction method affects not only the physico-chemical properties but also the free radical scavenging activity of the fractions.